The effect of carbohydrate feeding on the sprint performance of female cyclists following 50 minutes of high intensity exercise - Jarvis, A. T.; Felix, S. D.; Sims, S.; Coughlin, M.; Jones, M. T.; Headley, S. A. (Medicine & Science in Sports & Exercise, 1997)
The effect of periodic carbohydrate (CHO) feeding during exercise on the short term, high intensity exercise performance of trained female cyclists (N = 10) was studied. Two time-trials of 50 min, each followed by a Wingate Anaerobic Power Test to measure sprint capacity, were performed. Ss consumed 2 ml/kg of either a 7% CHO-electrolyte fluid replacement beverage or an aspartame-water placebo at 10, 20, 30, and 40 min into each trial. There were no differences in simulated sprint performance between the trials under the two conditions. However, there were differences across time in lactate accumulation and plasma glucose in the CHO-electrolyte condition when compared with the placebo condition in the time-trial exercise. These findings are different to a similar study conducted on male cyclists. Implication. Female cyclists were not able to improve sprint performance following a high intensity time trial of 50 min despite CHO feeding. These findings illustrate yet a further feature of male-female differences in exercise performance and function. Females do not respond to CHO supplementation and loading in a manner or magnitude similar to males.